Quetiapine augmentation in patients with treatment resistant obsessive-compulsive disorder: a single-blind, placebo-controlled study - Atmaca, M; Kuloglu, M; Tezcan, E; Gecici, O (Lippincott Williams & Wilkins, 2002)
Recently, atypical antipsychotics have been used for the management of the patients with refractory obsessive compulsive disorder (OCD). The aim of the present studs was to evaluate the results of quetiapine augmentation to a serotonin reuptake inhibitor (SRI) in the patients with refractory OCD. Fifty-two patients with OCD according to DSM-IV entered 3 months of an open-label phase treatment with a SRI with or without concomitant adjunctive treatment regimen. Of them, 27 patients were refractory OCD. These patients were randomly divided into two groups, SRI plus quetiapine and SRI plus placebo. for an 8-week single-blind phase. The course of OCD was evaluated by Yale-Brown Obsession-Compulsion (Y-BOCS) and Clinical Global Impression-Severity of Illness and Improvement (CGI-SI and I) Scales every other week for 8 weeks. Of the 14 patients in group I, nine (64.4%) showed significant improvement with 60% or greater improvement on the Y-BOCS and one (7.1%) partial improvement with 30% or greater improvement on the Y-BOCS, whereas no improvement was observed in group II. The addition of quetiapine to ongoing SRI therapy has been found to be effective and well-tolerated approach in patients with refractory OCD. Int Clin Psychopharmacol 17:115-119 (C) 2002 Lippincott Williams Wilkins.
Keywords: augmentation; OCD; quetiapine; refractory; SRI